Taxonomy of the ’Afroeudesis group’ of glandulariine ant-like stone beetles (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2019)
Among the currently recognized 71 extant genera of Glandulariini, Afroeudesis Franz shows an unusual distribution, with strikingly similar species known from South America, west and east Africa, and the sub-Himalayan region of Asia. Morphological studies revealed that several species placed in other genera share with Afroeudesis several unique characters, among others a symmetrical pattern of numerous setae on the frons and vertex, not known in any other Glandulariini. This ’Afroeudesis group’ is here recognized to be composed of the Neotropical genera Meridaphes Jałoszyński, Stenichnoconnus Franz and Pseudoraphes Franz, the broadly distributed Afroeudesis, and the Neotropical Bicarinulodes gen. n. The last is proposed for a species previously misplaced in Microscydmus Saulcy & Croissandeau, resulting in Bicarinulodes meridensis (Franz) comb. n. Bicarinulodes is most similar to Afroeudesis, but (among other differences) it lacks the apomorphy that is unique for the latter genus, the raised subtriangular ’platform’ on the frons and vertex. Stenichnoconnus minor (Franz), comb. n is proposed for Euconnus minor (Franz), originally published as Venezolanoconnus minor Franz. Stenichnoconnus and Pseudoraphes are redefined and redescribed.